Safety and quality improvement of street food packaging design using quality function deployment - Mohamad, Effendi; Faishal, Muhammad; Adiyanto, Okka; Abdul Rahman, Azrul Azwan; Jamli, Mohamad Ridzuan; Desviane, Shabilla; Ramawan, Alfian (Penerbit Universiti Tun Hussein Onn Malaysia, 2021)
Product packaging shows product detail and characteristics and can influence consumer desire. A wellpackaged product, when seen or felt, improves product perception and attitude. In Yogyakarta, fried meatballs are popular street food. Customers often complain about packaging post-purchase. Customers have often complained about the packaging and the common concerns are ‘hot to touch’ and ‘easily damaged packaging’. This study proposes to study the effect of consumer perception and attractiveness of the fried meatballs by improving the packaging. The Quality Function Deployment (QFD) technique was used during the designing phase to study consumer behaviour and desire to create attractive product packaging in line with customer expectations. Survey results indicated eight significant characteristics for fried meatball packaging. Those are; an attractive design, oil resistance, heat resistance, easy-to-handle packaging, durable material, food-grade packaging, environmental friendliness, and practical carrying ability. The eight attributes were reduced to five using QFD methodology and these five attributes are used as reference points for the development of better packaging. These five attributes of packaging design are; heat resistance, oil resistance, food-grade material, environmental friendliness, and not easy to tear. SolidWorks software was used to create 3D models. The design process was controlled to achieve the House of Quality (HOQ) target for consumer desire.